PENERAPAN MODEL PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA PADA MATA KULIAH PENDAHULUAN FISIKA INTI - Febriani Hastini Nasution (Jurnal Education and Development, 2017)
The purpose of this research was to determine the improvement of student’s concept understanding in Pendahuluan Fisika Inti subject. The research method was quasi experimental with one group pre-test-post-test design. The population was all of students in physics study program semester VII STKIP Tapanuli Selatan totalling 25 students and and all of population became sample in this research. The technique of sampling was total sampling. Based on the data tabulation obtained the actual average gain for implementing of Probem Based Instruction (PBI) model in improving student’s concept understanding was 30.84 where the normalized gain for implementation of PBI model to student’s concept understanding was 0,309, it was included in medium category. Based on the obtained results can be concluded that Implementation of Problem Based Instruction (PBI) model in Pendahuluan Fisika Intisubject was included in medium category to improve student’s concept understanding.